2014
DOI: 10.1371/journal.pone.0086937
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of αB-Crystallin Expression in Heat-Stressed Myocardial Cells In Vivo and In Vitro

Abstract: Relationships between αB-crystallin expression patterns and pathological changes of myocardial cells after heat stress were examined in vitro and in vivo in this study using the H9C2 cell line and Sprague-Dawley rats, respectively. Histopathological lesions, characterized by acute degeneration, karyopyknosis and loss of a defined nucleus, became more severe in rat hearts over the course of heat stress treatment from 20 min to 100 min. The expression of αB-crystallin in rat hearts showed a significant decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…Our previous research confirmed short term exposure to heat stress (1 h) induced detectable levels of enzymes related to heart damage, such as AST, CK and CKMB, in both the serum of rat blood and supernatant of rat myocardial cells938. Furthermore, pathological lesions, mainly due to necrosis, were observed in the rat myocardium after 40 min of heat stress in vivo , accompanied by lower CryAB expression, indicating CryAB may play an important role to protect the mammalian heart against heat stress21. In the present research, we investigated the expression profile of CryAB in the chicken myocardium using in vivo and in vitro models of heat stress lasting up to 24 h. Furthermore, we assessed the ability of ASA to protect the myocardium during heat stress, as it has been identified that the drug may protect the heart from heat stress by inducing Hsp90 and HspB1 expression39.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Our previous research confirmed short term exposure to heat stress (1 h) induced detectable levels of enzymes related to heart damage, such as AST, CK and CKMB, in both the serum of rat blood and supernatant of rat myocardial cells938. Furthermore, pathological lesions, mainly due to necrosis, were observed in the rat myocardium after 40 min of heat stress in vivo , accompanied by lower CryAB expression, indicating CryAB may play an important role to protect the mammalian heart against heat stress21. In the present research, we investigated the expression profile of CryAB in the chicken myocardium using in vivo and in vitro models of heat stress lasting up to 24 h. Furthermore, we assessed the ability of ASA to protect the myocardium during heat stress, as it has been identified that the drug may protect the heart from heat stress by inducing Hsp90 and HspB1 expression39.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, these experiments clearly indicated that overexpression of Hsp90 protected against a number of stimuli1920. Our other studies21 indicated overexpression of Hsp70 exerted a protective effect against heat stress2223. Therefore, these studies indicate the individual Hsps exert specific protective effects and their functions should be assessed separately.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…This therefore indicated that H9c2 cells and myocardial cells were protected from damage, particularly at the beginning of heat stress. These results were comparable with the findings of previous studies (32,33). It has been reported that increased levels of AST and LDH were associated with heart disease (34), the proposed mechanism of this is thought to be due to external stresses that may damage myocardial cell membranes, leading to the release of CK into the supernatant in vitro (35).…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the expression of myocardial cell damage-related enzymes and pathological changes, which have been validated by previous studies in our laboratory (Tang et al 2013(Tang et al , 2014Wu et al 2015), oxidative stress factors like SOD and MDA (Altan et al 2003;Paul et al 2009) along with the rates of apoptosis and necrosis (Green 2011;Masri and Chandrashekhar 2008) have also been suggested to respond to HS. However, in the present study, the oxidative stress indicators and apoptosis rate did not accurately reflect the myocardial cell damage.…”
Section: Discussionsupporting
confidence: 59%